Posthumous interest in the גאל הדם‎ legal tradition. (June 2019) - Imray, Kathryn
Scholarly reasons for the existence of the גאל הדם‎ institution tend to pool around the interests of three parties: the family or clan of the dead person, the Israelite people en masse, and the land those people possess. There is, however, another party with an interest in the death of the murderer, and that is the murdered person. To suggest that the dead have an interest in the execution of their killer is to argue for a belief in posthumous interests, a position here defended with reference to Israelite interment practice, and to Mesopotamian and Israelite beliefs about the dead and the violently dead.